2020
DOI: 10.1007/978-3-030-59719-1_53
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting 3D Context Modeling with Supervised Pre-training for Universal Lesion Detection in CT Slices

Abstract: Universal lesion detection from computed tomography (CT) slices is important for comprehensive disease screening. Since each lesion can locate in multiple adjacent slices, 3D context modeling is of great significance for developing automated lesion detection algorithms. In this work, we propose a Modified Pseudo-3D Feature Pyramid Network (MP3D FPN) that leverages depthwise separable convolutional filters and a group transform module (GTM) to efficiently extract 3D context enhanced 2D features for universal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In this study we demonstrated the reproducibility and generalizability of the model by testing through internal and external validation. To the best of our knowledge, there have been some AI algorithms developed that are capable of identifying multiple abnormalities, [22][23][24] but validations in real-world practice have been scarce, and this study is the first one to develop universal lesion detection model with internal and external validation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we demonstrated the reproducibility and generalizability of the model by testing through internal and external validation. To the best of our knowledge, there have been some AI algorithms developed that are capable of identifying multiple abnormalities, [22][23][24] but validations in real-world practice have been scarce, and this study is the first one to develop universal lesion detection model with internal and external validation.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation Details: All the compared methods take 9 consecutive slices as input, which can be represented as a gray-scale 3D tensor of 1 × 9 × 512 × 512. Since only 2D annotations (2D bounding boxes on the key slice) are provided in the DeepLesion dataset, we use a similar architecture as MP3D [32] for lesion detection. MP3D neglects all the downsampling operations for the z-axis to keep the depth of all backbone outputs as 9.…”
Section: E Universal Lesion Detectionmentioning
confidence: 99%
“…Anchor scales of FPN are set to (16,32,64,128,256) to improve detection performance for small lesions. We apply multi-scale training with scales randomly sampled from (384, 448, 512, 576, 640).…”
Section: E Universal Lesion Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Universal Lesion Detection (ULD) in computed tomography (CT) [1][2][3][4][5][6][7][8][9][10][11][12][13], which aims to localize different types of lesions instead of identifying lesion types [14][15][16][17][18][19][20][21][22][23][24][25], plays an essential role in computer-aided diagnosis (CAD). ULD is a challenging task because different lesions have very diverse shapes and sizes, easily leading to false positive and false negative detections.…”
Section: Introductionmentioning
confidence: 99%